DAMPAK PEMIKIRAN ORIENTALIS DI INDONESIA PADA MASA KOLONIAL - Syukri Syukri (FiTUA: Jurnal Studi Islam, 2021)
The Indonesian people had been colonized by the Dutch for 360 years. During that time, many things were done by the Dutch towards Indonesia. The policies issued by the Dutch were much influenced by the advice given by their political advisors. Political advisers (Orientalists) who are quite well known are Stanford Thomas Raffles, William Masrden, and Cristian Snouck Hurgronje. These three political advisors gave accurate advice to the Dutch government in order to influence patterns of social life in Indonesian society. In the field of religion, especially Islam, Thomas S. Raffles and Marsden argue that the teachings of Islam do not give the slightest color to Indonesian culture. Indonesian culture is purely dug out of local customs. Yet in reality, it is the teachings of Islam that characterize the lives of Indonesian people. In the political field, the Dutch were able to conquer the Aceh region on the advice of Snouck Hurgronje who had previously mastered the ins and outs of the Aceh region. In the area of ​​customary law, Snouck with his receptie theory says that indigenous peoples basically only apply customary law; Islamic law can only apply if the norms of Islamic law have been accepted by the community as Adat law. The receptie-Snouck theory, after independence, can be broken by indigenous jurists by proposing their own theories, namely; first, the receptie exit theory by Hazairin. Second, the theory of receptio a contrario by H. Sayuti Thalib, and Third, the theory of existence by H. Ichtijanto SA.